Fishing Catch and Catch Rate Assesment of Mini Trawl, Trapnet and Setnet Fisheries - Firdaus, Muhammad (Makara Journal of Technology, 2010)
Fishing Catch and Catch Rate Assesment of Mini Trawl, Trapnet and Setnet Fisheries. This paper is aimed at assessing fishing catch and catch rate of the dragged gear on shrimp, trapnet, and setnet fisheries in Tarakan. The catch and effort data (number and species) and the fishing time of captured units were used in this qualitative analysis of fishing catch and catch rate to describe catch composition and catch rate from three catch fishery units in Tarakan. The result of the research shows that in the catching operation the dragged gear on shrimp has two main catch targets, which are the nomei fish and shrimp in the their two fishing seasons. The nomei fish is also the main catch target in the trapnet fishery, and the pelagic fish inhabiting the estuary and the coastal areas are the main catch target of the setnet fishery. The operation of the dragged gear on shrimp with nomei fish as the main catch target has a catch rate of 16.10 kg/hour and that in the trapnet fishery is 1.67 kg/hour. The catch rate of setnet fishery is 5.39 kg/day and the operation of the dragged gear on shrimp with shrimp as the main catch target has a catch rate of 2.05 kg/hour.